Rehabilitation Using a Systematic and Holistic Approach for the Injured Athlete Returning to Sport - Ethan Paster, P.T., D.P.T., S.C.S., C.S.C.S; Alfredo Sayeg, P.T., D.P.T; Scott Armistead, M.S., L.A.T., A.T.C; Michael D. Feldman, M.D (Elsevier, 2022)
The purpose of this article is to identify gold standards of care for return to sport following athletic injury, investigate overlooked aspects of return to sport rehabilitation, and provide expert opinion regarding current practices. The article was written by performing a literature review, then providing editorial expert opinion regarding current standards of return to sport. We concluded, through literature review and expert consensus, that a three-pronged approach to return to sport is recommended for therapists. These three prongs are ROM, strength, and hop testing. Cardiovascular readiness and psychological readiness for return to sport must also be assessed."